Los terremotos, el crecimiento económico y el desarrollo - Vega-Centeno, Máximo (2011)
This paper aims to set decision framework for the earthquake preventions measures. The starting point is the differences between the natural phenomenon and the disaster; although both have frequency in common, the last one is more unpredictable, but in both cases is a question to make probability estimation. In other words, the earthquakes in Peru appear suddenly and they are an inevitable and repetitive phenomenon. According to that, a better prevention measures can be taken, in order to reduce the economical impact, mainly for the lower income people and improving the quality of life for them in social and human terms. Under such conditions, the absences of an adequate policy on this matter make people unsure about their future and this is a brake for human development